Seagrass restoration in the greater Southeast Asia region: techniques, species, survival and comparisons among investigations - Thorhaug, Anitra; Verduin, Jennifer Joan; Kiswara, Wawan; Prathep, Anhana; Huang, Xiaoping; Gallagher, John Barry; Yap, Tzuen-Kiat; Ambo-Rappe, Rohani; Dorward, Susan E.; Schwarz, Arthur; Berlyn, Graeme P. (Frontiers in Marine Science, 2025)
The greater Southeast Asian region contains the largest global extent of tropical seagrass; however, anthropogenic degradation is estimated to be greater than 7% per year. Although the areal extent of seagrass is presently 36,765 km2, Fortes group estimates that 50% of the original seagrass has been degraded from a variety of impacts. One set of solutions to degradation is to restore tropical seagrass successfully, for which information from past results is needed to avoid failures. Van Katwijk, Thorhaug and others provided a global seagrass restoration review of 1,786 trials, but did not include the full Southeast Asian regional information. Thus, we review findings from 228 trials in the greater Southeast Asian region, involving 305,807 restored units with an extent of 372,649 m2. Seagrasses planted with varying successes include 13 tropical species and five subtropical or near-subtemperate species. We compare methodologies as well as key factors of light level, energetics, and depth. This review demonstrates the highest survival in seagrass restoration employing sprigs or plugs at medium depths (2–4 m) with adequate light levels in medium to low energetics planting one to several dominant species. Substrate anchors improved successful establishment. Information gaps occur in quantified monitoring of seagrass services reassembled with tropical-seagrass restoration; thus, fisheries’ nursery potentials are not provided. Future actions need national seagrass restoration policies and plans to restore degraded seagrasses. At present, such policies and plans are non-existent in most greater Southeast Asian regional nations, with the exceptions of Australia and the Philippines, although some nations have national plans for restoring corals or mangroves.